Status of children's sections of selected city public libraries in District II and District III of Metro Manila with implications towards the development of guidelines for services, staffing and collection development - Aguinaldo, Marjorie E. (School of Library and Information Studies, University of the Philippines Diliman, 2016)
A public library must serve everyone in the community, including the children. To meet the needs of the children, public libraries usually have a children's section which contains various information materials for children. This study sought to determine the current status of the children's section of selected city public libraries in District II and III of Metro Manila and developed a guideline for the services, staffing, and collection development of the children's section based on the perception of library staff responsible for the children's section of the public libraries.